2016
DOI: 10.1038/srep27578
|View full text |Cite
|
Sign up to set email alerts
|

Two endoplasmic reticulum proteins (calnexin and calreticulin) are involved in innate immunity in Chinese mitten crab (Eriocheir sinensis)

Abstract: Calnexin (Cnx) and calreticulin (Crt), which are important chaperones in the endoplasmic reticulum (ER), participate in the folding and quality control of client proteins. Cnx and Crt identified from Chinese mitten crab (Eriocheir sinensis) are designated as EsCnx and EsCrt, respectively. EsCnx and EsCrt are expressed in the hemocyte, hepatopancrea, gill, and intestine at the mRNA and protein level. Immunofluorescence analysis indicated that EsCnx and EsCRT are located in the ER. Moreover, the mRNA and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…In this sense, T1 allowed activating a conservative response. The results showed that T1 also up-regulated genes related to sense microbial viability (STING), which allowed organisms to detect living bacteria [77], bind Vibrio protein (CALR) that can be released from the cell and neutralise vibrio [78,79] and heat shock proteins (HSP70 and HSP90), related to showing antigen (adaptive immune system) [80], protein fold [81], activating Toll-like receptors [82] and mediating immune response in bacterial challenges [83]. The above suggested that T1 allowed the activation of pathways related to recognition, neutralisation, internalisation and destruction of Vibrio.…”
Section: Plos Onementioning
confidence: 99%
“…In this sense, T1 allowed activating a conservative response. The results showed that T1 also up-regulated genes related to sense microbial viability (STING), which allowed organisms to detect living bacteria [77], bind Vibrio protein (CALR) that can be released from the cell and neutralise vibrio [78,79] and heat shock proteins (HSP70 and HSP90), related to showing antigen (adaptive immune system) [80], protein fold [81], activating Toll-like receptors [82] and mediating immune response in bacterial challenges [83]. The above suggested that T1 allowed the activation of pathways related to recognition, neutralisation, internalisation and destruction of Vibrio.…”
Section: Plos Onementioning
confidence: 99%
“…In addition to the phagocytotic effects of CALR in antitumor responses, CALR has also an important role in the pathogenesis of infectious and autoimmune diseases. CALR interacts with lipopolysaccharide (LPS), a component of the gram-negative bacterial cell wall via the N-and C-domain globular head region and the C-domain alone, participating in LPS-mediated anti-bacteria innate immunity (33,34). In addition, CALR participated in pathogenetic inflammation through activation of integrin alpha subunits (ITGAs) and subsequently increasing adhesion and infiltration of both T cells and neutrophils (11).…”
Section: Introductionmentioning
confidence: 99%
“…Calnexin can escape from the ER and be transported to the plasma membrane or released into the extracellular space by interacting with glycoproteins (15)(16)(17) or via its phosphorylation at two serine residues (Ser554/564) by protein kinase CK2 (18). Some studies have found that extracellular calnexin could be involved in innate and adaptive immunity in non-mammals (19)(20)(21), but the impact of surface or secreted calnexin on the human immune system has not been reported. The results from a lung cancer patient cohort provided evidence that calnexin may be a serodiagnostic marker for lung cancer (15).…”
Section: Introductionmentioning
confidence: 99%